2023
DOI: 10.3390/ijms242115849
|View full text |Cite
|
Sign up to set email alerts
|

AML under the Scope: Current Strategies and Treatment Involving FLT3 Inhibitors and Venetoclax-Based Regimens

Szymon Milnerowicz,
Julia Maszewska,
Paulina Skowera
et al.

Abstract: Acute myeloid leukemia (AML) is a disease that mainly affects elderly patients who are more often unfit for intensive chemotherapy (median age of diagnosis is 68). The regimens, including venetoclax, a highly specific BCL-2 (B-cell lymphoma-2) inhibitor, are a common alternative because of their safer profile and fewer side effects. However, the resistance phenomenon of leukemic cells necessitates the search for drugs that would help to overcome the resistance and improve treatment outcomes. One of the resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…The combination of venetoclax with other drugs, such as azacitidine and decitabine, has been shown to signi cantly improve the rate of complete remission and patient survival. However, when used as a monotherapy, its e cacy is limited (Milnerowicz et al 2023). In addition, a signi cant proportion of patients exhibit primary or acquired resistance to venetoclax (Dhakal et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of venetoclax with other drugs, such as azacitidine and decitabine, has been shown to signi cantly improve the rate of complete remission and patient survival. However, when used as a monotherapy, its e cacy is limited (Milnerowicz et al 2023). In addition, a signi cant proportion of patients exhibit primary or acquired resistance to venetoclax (Dhakal et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of venetoclax with other drugs, such as azacitidine and decitabine, has been shown to significantly improve the rate of complete remission and patient survival. However, when used as a monotherapy, its efficacy is limited (Milnerowicz et al 2023 ). In addition, a significant proportion of patients exhibit primary or acquired resistance to venetoclax (Dhakal et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…BCL-2 is an antiapoptotic protein that is overexpressed in AML cells and promotes leukemic blast survival through regulation of the mitochondrial apoptotic pathway . Venetoclax (VEN), a highly selective BCL-2 inhibitor, in combination with hypomethylating agents or low-dose cytarabine has been approved as a standard option for newly diagnosed AML patients who are unfit for intensive chemotherapy. Recent studies have indicated the synergistic effect of VEN in combination with FLT3 inhibitors in FLT3-ITD AML models, , likely due to the simultaneous downregulation of MCL-1 and BCL-XL antiapoptotic proteins, which can facilitate VEN resistance. , Moreover, early phase clinical trials have shown encouraging response rates and survival benefits in FLT3 mutant AML patients after combination therapy with VEN and FLT3 inhibitors. Nevertheless, this combination is associated with poor bioavailability, dose-dependent myelosuppression, overlapping systemic toxicity, and drug resistance, limiting its clinical benefits.…”
Section: Introductionmentioning
confidence: 99%